Age of volcanism on Keller Peninsula and assessment of age‑constrained volcanic activity on King George Island, West Antarctica - Nawrocki, Jerzy; Pańczyk, Magdalena; Wójcik, Krystian; Kozłowska‑Roman, Agata (Polish Polar Research, 2021)
Studies of isotopic ages were conducted for rock samples of the Keller, Visca Anchorage and Domeyko Glacier formations. Together they form a part of the Martel Inlet Group, a terrestrial calc‑alkaline volcanic and volcanoclastic suite and they crop out along the Keller Peninsula on King George Island. The U‑Pb and 40Ar/39Ar isotope data from the Keller Peninsula lava flows, although differing in quality, made it possible to obtain reliable age intervals. The stratified volcanogenic rocks of Keller Peninsula, Visca Anchorage and Domeyko Glacier formations of the Keller Peninsula were emplaced there near the Early/Late Palaeocene boundary (ca. 62.11 ± 0.66 Ma ago), in the Early Eocene (ca. 56.3–51.9 Ma) and near the Early/Middle Eocene boundary (ca. 49.9–47.9 Ma), respectively. A certain difference in the ages of Eocene volcanogenic formations, in particular tectonic blocks of King George Island, may indicate a migration of centres of volcanic activity over time, from northwest to southeast.